Germans on welfare : from Weimar to Hitler - Crew, David F. 1946- (Oxford University Press, 1998)
Introduction: The Meaning of the German Welfare State -- 1. Religion, Socialism, and State Welfare in the Weimar Republic -- 2. The Welfare System in the Neighborhoods: Professionals and Volunteers -- 3. The Gender of Welfare: Women and Social Work -- 4. Becoming a Welfare Client -- 5. Pensioners in the Welfare System -- 6. Weimar Women on Welfare -- 7. The State as Parent? Youth Welfare and German Families -- 8. The Weimar Welfare State's Last Crisis, 1929-1933 -- 9. Hungry and Homeless in the Depression -- 10. "Welfare Is the Preservation of Labor Power": Unemployment and Work Relief -- Conclusion: Toward the Nazi Racial State